Study on the implementation of MS1998:2017 - good aquaculture practices for small-scale tilapia farmers in Selangor / Nur Safirah Sapuan - Nur Safirah , Sapuan (2023)
Fisheries have been a long-established way for humanity to obtain food. As the world’s top natural protein provider in the diet of many nations, it has retained its significance, with 75% of global fish production being intended for direct human consumption. One of the government’s initiatives to improve food security is encouraging agriculture players to meet the Good Aquaculture Practices (GAqP) standard in getting the Malaysian Good Agricultural Practices (MyGAP) certificate. Participation in meeting GAqP standards will also assist smallholders in achieving maximum yield. However, small-scale fish farmers are having difficulties achieving the GAqP standards. This study was carried out to investigate such difficulties faced by the farmers in meeting GAqP standards. 30 out of 58 small-scale fish farmers in Selangor were used in this study. Their compliance with GAqP standards was evaluated together with their economic return. Benefit-Cost Ratio (BCR) projection and regression analysis were carried out to determine the economic return in an attempt to comply with the GAqP standards. The finding shows that the average BCR for smallholder aquaculture farms for a 5-year period was estimated at 1.23, and 64.7% of the GAqP standard complied. At the moment, the economic return was found to be profitable. Better economic return can be expected when the percentage of compliance increases. This study implies that greater commitment from both the government and fish farmers is needed in order to overcome the challenges of meeting the GAqP standards.